Functionalized porous Si nanowires for selective and simultaneous electrochemical detection of Cd(II) and Pb(II) ions. (1st September 2016) - Guo, Zheng; Seol, Myeong-Lok; Gao, Chao; Kim, Moon-Seok; Ahn, Jae-Hyuk; Choi, Yang-Kyu; Huang, Xing-Jiu
Graphical abstract: Through a typical Ag-assisted etching approach combined with chemical modification, thiol- and amino-functionalized porous Si nanowires have been synthesized. Their modified electrodes successfully realize individual and simultaneous electrochemical detection of Cd(II) and Pb(II) without any interference, owing to the selective interaction of thiol and amino groups toward them. Abstract: Thiol and amino-functionalized porous Si nanowires have been demonstrated to selectively detect Cd(II) and Pb(II) with high sensitivity using square wave anodic stripping voltammetry (SWASV) analysis. Through a typical Ag-assisted chemical etching approach, uniform and porous Si nanowires have been fabricated on heavily doped Si wafer. Continuously functionalized by (3-mercaptopropyl)trimethoxysilane (MPTMS) and (3-aminopropyl)triethoxysilane (APTES), the internal and external surfaces of porous Si nanowires have been decorated with thiol and amino groups, respectively. Inspired by the intrinsic properties of porous nanostructures, their electrochemical performances toward heavy metal ions have been further evaluated. The results indicate that Cd(II) and Pb(II) can be detected with high sensitivity owing to the strong complexing capacity of thiol and amino groups. Additionally, porous Si nanowires decorated with thiol groups present different stripping behaviors from those with amino groups toward the investigated heavy metal ions, realizing the selective and simultaneous detection of Cd(II) and Pb(II). Furthermore, simultaneous detection of Cd(II) and Pb(II) has also been demonstrated without any interference and their individual high sensitivity has been fundamentally preserved. Expectedly, porous Si nanowires as an effective modifier can be further extended to selectively detect other heavy metal ions through modifying with other functional organic groups.